Separation of epistatic, additive and dominant effects on corn. - Mendoza, Mariano; López, Alfonso; Rodríguez, Sergio A.; De León, Carlos; Jeffers, Dan (Agronomía Mesoamericana, 2006)
The inheritance of host to stunt maize was studied under natural field conditions. Inbred lines P1 (moderately resistant) and P2 (susceptible) and their F1, F2, [BC(P1) and BC(P2)] progenies were evaluated at two seasons at sea level, in Veracruz in 1999. Significant epistatic effects were noted to the resistance to stunt corn; however, the dominant genetics effects were greater and more important than additive and epistatic effects. The data showed that resistance to stunt corn was controlled by only a few major genes. The F1 hybrid showed high tolerance, indicating dominance and mid-parent heterosis for resistance was also observed. The data indicate that a back-crossing procedure can be used to transfer the resistance factors into elite lines. Some form of recurrent selection in populations having a degree of resistance also is suggested.